CRASH and burn: abatement of a specialised gang unit. Issue 2 (13th June 2016) - Valasik, Matthew; Reid, Shannon E.; Phillips, Matthew D.
Abstract : Purpose: – The purpose of this paper is to examine the impact of the temporary disbandment of a gang unit on collecting gang intelligence and arresting gang members in one of the Los Angeles Police Department's Community Policing Areas. Design/methodology/approach: – An interrupted time series methodology (ARIMA) is utilised to examine 1, 429 field interview cards and 1, 174 arrests of gang members that occurred from 1 January 2010 to 31 December 2011 within one police division. Findings: – Results indicated that the dismantling of the gang unit negatively impacted the collection of intelligence on gang members by officers, regardless of whether the officers were officially serving in the gang unit. Suppression efforts by gang unit officers also resulted in a sustained decline. Originality/value: – Given that many urban centres have specialised gang units, this study demonstrates how organisational turnover or disbandment of a gang unit negatively impacts a department's ability to deal with local gang issues. Furthermore, these finding suggest that police organisations should consider such ramifications on intelligence-based policing activities.